Batman year one - Miller, Frank 1957-; Drake, Christopher (Warner Bros. Entertainment, 2011)
Comics legend Frank Miller's classic retelling of Batman's early days, depicting a young Bruce Wayne's return to Gotham City and his first endeavors at fighting injustice as Batman